Air quality impacts of a major wildfire in the UK: Sensitivity to model spatial resolution and transport method - Benjamin Drummond; Ailish Graham; Lucy Neal; Pedro Molina Jiménez; Richard J. Pope; Carly Reddington (Atmospheric Pollution Research, 2026)

Fishers' Local Ecological Knowledge Reveals Complex Food Web Dynamics With Rapidly Warming Waters - Loren McClenachan; Benjamin Neal; Marissa McMahan; Ellie Batchelder; Neida Villanueva‐Galarza; Jonathan Grabowski (Fish and Fisheries, 2025)
Local ecological knowledge (LEK) can provide insight into ecosystem change, particularly in dynamic ecological conditions, such as those driven by climate change. In New England lobster fisheries, warming waters have the potential to disrupt food webs, as range‐shifting species introduce novel ecological interactions. Here we use interviews with lobster fishers in Maine and Massachusetts to understand lobster fishers' LEK of dynamic food webs, taking a mental modelling approach to construct LEK food web models under rapidly warming waters. We find that fishers are observing a remarkable range of ecological interactions across habitats, collectively reporting knowledge of > 35 species that interact trophically with lobster across larval, juvenile, and adult life stages, ranging from terrestrial species like mink ( Neovison vison ) to deep sea species like redfish ( Sebastes fasciatus ). Our LEK food webs demonstrate perceptions of warming water altering species' abundances and interactions, with an overall negative impact on lobster fisheries. Fishers also report knowledge of complex interactions, including predation, competition, and habitat loss mediated by warming waters and changing species' abundances. Finally, we identify and categorise three main pathways that contribute to fishers' LEK, including observation, word of mouth, and inference. Our findings demonstrate that active fishers have complex understandings of food web interactions in dynamic ecosystems that are changing rapidly. With management unable to keep pace with climate‐driven change, fishers' LEK is an invaluable source of knowledge, whose use could improve the ability to understand the diverse impacts of warming waters on coastal ecosystems.

Sensitivity of North American grassland birds to weather and climate variability - Scott B. Maresh Nelson; Christine A. Ribic; Neal D. Niemuth; Jacy Bernath‐Plaisted; Benjamin Zuckerberg (Conservation Biology, 2024)
Grassland birds in North America have declined sharply over the last 60 years, driven by the widespread loss and degradation of grassland habitats. Climate change is occurring more rapidly in grasslands relative to some other ecosystems, and exposure to extreme and novel climate conditions may affect grassland bird ecology and demographics. To determine the potential effects of weather and climate variability on grassland birds, we conducted a systematic review of relationships between temperature and precipitation and demographic responses in grassland bird species of North America. Based on 124 independent studies, we used a vote‐counting approach to quantify the frequency and direction of significant effects of weather and climate variability on grassland birds. Grassland birds tended to experience positive and negative effects of higher temperatures and altered precipitation. Moderate, sustained increases in mean temperature and precipitation benefitted some species, but extreme heat, drought, and heavy rainfall often reduced abundance and nest success. These patterns varied among climate regions, temporal scales of temperature and precipitation (

Swine global genomic resources: insights into wild and domesticated populations - Neal R. Benjamin; Richard P. M. A. Crooijmans; Luke R. Jordan; Courtni R. Bolt; Lawrence B. Schook; Kyle M. Schachtschneider; Martien A. M. Groenen; Alfred L. Roca (Mammalian Genome, 2023)

Amphetamine alters an EEG marker of reward processing in humans and mice - James F. Cavanagh; Sarah L. Olguin; Jo A. Talledo; Juliana E. Kotz; Benjamin Z. Roberts; John A. Nungaray; Joyce Sprock; David Gregg; Savita G. Bhakta; Gregory A. Light; Neal R. Swerdlow; Jared W. Young; et al. (Psychopharmacology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

Amphetamine improves rat 5-choice continuous performance test (5C-CPT) irrespective of concurrent low-dose haloperidol treatment - Jared W. Young; Benjamin Z. Roberts; Michelle Breier; Neal R. Swerdlow (Psychopharmacology, 2020)

Shifting perceptions of rapid temperature changes’ effects on marine fisheries, 1945–2017 - Loren McClenachan; Jonathan H. Grabowski; Madison Marra; C. Seabird McKeon; Benjamin P. Neal; Nicholas R. Record; Steven B. Scyphers (Fish and Fisheries, 2019)
Climate‐driven warming has both social and ecological effects on marine fisheries. While recent changes due to anthropogenic global warming have been documented, similar basin‐wide changes have occurred in the past due to natural temperature fluctuations. Here, we document the effects of rapidly changing water temperatures along the United States’ east coast using observations from fisheries newspapers during a warming phase (1945–1951) and subsequent cooling phase (1952–1960) of the Atlantic Multidecadal Oscillation, which we compared to similar recent observations of warming waters (1998–2017). Historical warming and cooling events affected the abundance of species targeted by fishing, the prevalence of novel and invasive species, and physical access to targeted species. Fishing communities viewed historical cooling waters twice as negatively as they did warming waters (72% vs. 35% of observations). Colder waters were associated with a decrease in fishing opportunity due to storminess, while warming waters were associated with the potential for new fisheries. In contrast, recent warming waters were viewed as strongly negative by fishing communities (72% of observations), associated with disease, reductions in abundances of target species, and shifts in distributions across jurisdictional lines. This increasing perception that warming negatively affects local fisheries may be due to an overall reduction of opportunity in fisheries over the past half century, an awareness of the relative severity of warming today, larger changes in American culture, or a combination of these factors. Negative perceptions of recent warming waters’ effects on fisheries suggest that fishing communities are currently finding the prospect of climate adaptation difficult.

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Genetic structure and environmental niche modeling confirm two evolutionary and conservation units within the western spadefoot (Spea hammondii) - Kevin M. Neal; Benjamin B. Johnson; H. Bradley Shaffer (Conservation Genetics, 2018)

Managing an invasive corallimorph at Palmyra Atoll National Wildlife Refuge, Line Islands, Central Pacific - Thierry M. Work; Greta S. Aeby; Benjamin P. Neal; Nichole N. Price; Eric Conklin; Amanda Pollock (Biological Invasions, 2018)
In 2007, a phase shift from corals to corallimorpharians (CM) centered around a shipwreck was documented at Palmyra Atoll, Line Islands. Subsequent surveys revealed CM to be overgrowing the reef benthos, including corals and coralline algae, potentially placing coral ecosystems in the atoll at risk. This prompted the U.S. Fish and Wildlife Service, the lead management agency of the atoll, to remove the shipwreck. Subsequent surveys showed reductions in CM around the ship impact site. We explain patterns of spread of the CM in terms of both life history and local currents and show with a pilot study that pulverized bleach may be an effective tool to eradicate CM on a local scale. If applied strategically, particularly in heavily infested (> 66% cover) areas, active intervention such as this could be an effective management tool to reduce CM impact on localized areas and decrease colonization rate of remaining reefs. This is the first documentation of the response of an invasive cnidarian to shipwreck removal. While this was a singular event in Palmyra, the spatial and temporal patterns of this invasion and the eradications lessons described herein, are useful for anticipating and controlling similar situations elsewhere.

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Assessment of metal contamination in the biota of four rivers experiencing varying degrees of human impact - Gretchen K. Bielmyer-Fraser; Matthew Neal Waters; Christina G. Duckworth; Pratik P. Patel; Benjamin Cole Webster; Amber Blocker; Cliff Hunter Crummey; Aundrea Nicole Duncan; Somuayiro Nadia Nwokike; Codie Richard Picariello; James T. Ragan; Erika L. Schumacher; et al. (Environmental Monitoring and Assessment, 2017)

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

Response diversity to land use occurs but does not consistently stabilise ecosystem services provided by native pollinators - Daniel P. Cariveau; Neal M. Williams; Faye E. Benjamin; Rachael Winfree (Ecology Letters, 2013)
More diverse biological communities may provide ecosystem services that are less variable over space or time. However, the mechanisms underlying this relationship are rarely investigated empirically in real‐world ecosystems. Here, we investigate how a potentially important stabilising mechanism, response diversity, the differential response to environmental change among species, stabilises pollination services against land‐use change. We measured crop pollination services provided by native bees across land‐use gradients in three crop systems. We found that bee species responded differentially to increasing agricultural land cover in all three systems, demonstrating that response diversity occurs. Similarly, we found response diversity in pollination services in two of the systems. However, there was no evidence that response diversity, in general, stabilised ecosystem services. Our results suggest that either response diversity is not the primary stabilising mechanism in our system, or that new measures of response diversity are needed that better capture the stabilising effects it provides.

The binding of analogs of porphyrins and chlorins with elongated side chains to albumin - Shimshon Ben Dror; Irena Bronshtein; Hana Weitman; Kevin M. Smith; William G. O’Neal; Peter A. Jacobi; Benjamin Ehrenberg (European Biophysics Journal, 2009)